Ammonia and pH inhibition in anaerobic treatment of wastewaters, part I: Experimental - ÇALLI, BARIŞ (TAYLOR & FRANCIS INC, 2004)
The influences of pH and ammonia on methane production in the anaerobic treatment of in acetic-propionic-butyric acid mixture in batch reactors operated at 37degreesC were investigated. Two independent sets of experiments were carried out using seeds from two different full-scale industrial anaerobic treatment reactors. One of the seeds (Sludge A) was obtained from an upflow anaerobic sludge-blanket (UASB) reactor treating the waste from a potato chips production plant. The second sludge seed (Sludge B) was from an expanded granular sludge-blanket (EGSB) reactor treating a corn processing waste. Experiments were carried out at four different pH values (6.8, 7.4 7.8, 8.4) and with six different TAN (Total Ammonia Nitrogen) values (262mg/L (control), 1000, 1500, 2000, 2500, 3000). Three vials (triple runs) were used for each pH and TAN value. The sludge seeds used in the inhibition tests were not exposed to high levels of ammonia at any stage before the tests. For each vial, cumulative methane production was monitored for a period long enough for the termination of biogas production. Although neither sludge was acclimated to ammonia, the lag-phase times were less than 2 days for Sludge A and essentially zero for Sludge B for all TAN and pH values. At certain high pH and high TAN values, however, methanogenic activity ceased within about 1-3 months; and then activity restarted and methane formation rate reached its maximum values after this period. If the experiments had not been continued following this period, this reactivation phenomenon would not have been detected.
Keywords: ammonia inhibition; anaerobic treatment; mesophilic; methanogenesis; METHANOGENIC SLUDGE; METHANE PRODUCTION; CATTLE MANURE; DIGESTION; NITROGEN; TOXICITY; GROWTH; DEGRADATION; ADAPTATION; WASTES